Be wiser in choosing disinfectant product - UMP, PNC (2020)
Due to the outbreaks of COVID-19 in many countries around the globe, including Malaysia, items like disinfectant liquid, face mask, face shield and personal protective equipment are becoming more difficult to find in the market.